Persepsi Pemilik Usaha Terhadap Sistem Go-Send dan Go-Food - I Wayan Gede Andy Wirawan; A.A.N. Eddy Supriyadinata Gorda (Jurnal Manajemen dan Bisnis, 2019)
ABSTRACTPerception is how someone's point of view to see or interpret something, in the business world this is certainly very influential to determine the best strategy for a developing business. In this study, it explains how business owners' perceptions of brand image are caused by the service quality of the Go-Send and Go-Food systems in the Go-Jek application. In the perception of the researcher to see from the perspective of the business owner about the influence of the quality of service from Go-Jek on the image of the business brand. This research is a qualitative research that is by describing the phenomena that occur in the field by knowing the perceptions of business owners.In this study the data collection uses interviews directly to competent informants and documentation of activities that are useful as tangible evidence of activity on the object under study. The informants in this study were eight people. The results of this study are that business owners feel helped in terms of promotion and product introduction and business owners can overcome problems in service quality in product delivery.